A critical investigation into discourses that construct academic literacy at the Durban Institute of Technology - McKenna, Sioux (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2004)
This thesis examines the construction of academic literacy at the Durban Institute of Technology through a discourse analysis of interviews with educators and learners. Academic literacy comprises the norms and values of higher education as manifested in discipline-specific practices. Students are expected to take on these practices, and the underlying epistemologies, without any overt instruction in, or critique of, these ways of being. Lecturer and student discourses are identified and discussed in terms of their impact on the teaching and learning process. This broad context of educator and student understandings is set against the backdrop of the changing educational policies and structures in post-Apartheid South Africa. The changes in approach to academic development are also traced as a setting for the institutional study. The discourses about the intersection between language and learning were found largely to assume that texts, be they lectures, books, assignments etc, are neutral and autonomous of their contexts. Difficulties some learners experience in accessing or producing the expected meaning of these texts were largely ascribed to their problems with language at a surface level rather than to their lack of shared norms regarding the construction of these texts. The study provides an analysis of how the 'autonomous' model is manifested iii and illustrates the limitations on curriculum change imposed by this understanding of how texts are constructed and interpreted. Discourses of motivation presume that students' difficulties in taking on the literacy practices esteemed by the academy are related to attitude. This discourse assumes that learners have a fairly fixed identity, an assumption that did not bear out in the data. The multiple identities of the learners often presented tensions in the acquisition of discipline-specific academic literacies. The learners were found not to invest strongly in an academically literate identity, or were found to experience conflict between this target identity and the identities they brought with them to the institution. The elevation of academic literacy practices is questioned if the surface features, characteristic of these practices, are valued without a concomitant claim to knowledge production. The rapid emergence of a high skills discourse in Universities of Technology in South Africa is also interrogated, given the current emphasis on training for economic growth over discourses of social redress and transformation.
Keywords: Uncatalogued